2005
DOI: 10.1111/j.1525-1497.2005.05049.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceived discrimination in clinical care in a nationally representative sample of HIV-infected adults receiving health care

Abstract: Background: Perceived discrimination in clinical settings could discourage HIV‐infected people from seeking health care, adhering to treatment regimens, or returning for follow‐up. Objectives: This study aims to determine whether HIV‐infected people perceive that physicians and other health care providers have discriminated against them. Design, Participants: Cross‐sectional data (1996 to 1997) from the HIV Cost and Services Utilization Study (HCSUS), which conducted in‐person interviews with a nationally r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
107
1
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 199 publications
(115 citation statements)
references
References 75 publications
3
107
1
4
Order By: Relevance
“…While a few scales exist to measure perceived stigma specifically from health care providers (Bodenlos et al, 2004;Kinsler et al, 2007;Schuster et al, 2005), other existing measures of stigma in PLHA do not include items that also address stigma in the context of HIV treatment. We found stigma in the health care setting and related to ART to be highly relevant in our formative work and the peer-reviewed literature, and we have included items in our measure that tap these concepts (items 1, 10, 13, 14, 1, 18, 19).…”
Section: Discussionmentioning
confidence: 99%
“…While a few scales exist to measure perceived stigma specifically from health care providers (Bodenlos et al, 2004;Kinsler et al, 2007;Schuster et al, 2005), other existing measures of stigma in PLHA do not include items that also address stigma in the context of HIV treatment. We found stigma in the health care setting and related to ART to be highly relevant in our formative work and the peer-reviewed literature, and we have included items in our measure that tap these concepts (items 1, 10, 13, 14, 1, 18, 19).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] From 1994 to 1998, Centers for Disease Control and Prevention (CDC) surveys found that 14% of adolescent and young adult African American MSM participants (n ¼ 4000) were infected with HIV. 4 More recent CDC findings raise further concern, suggesting a 93% increase in the number of HIV/AIDS cases among African American MSM aged [13][14][15][16][17][18][19][20][21][22][23][24] years between 2001 and 2006. 5 These alarming statistics highlight the urgent need for HIV/AIDS prevention efforts targeting young African American MSM.…”
mentioning
confidence: 99%
“…5,6 HIV-related stigma and discrimination have also been identified as barriers to seeking appropriate healthcare for people living with HIV. 7,8 In a study of HIV-positive adolescents, half of participants reported skipping medication doses to avoid disclosure of HIV status to friends and family. 9 Other authors have clearly linked experience of HIV stigma with increased rates of depression.…”
mentioning
confidence: 99%